Re‐emergence of circulatory foot‐and‐mouth disease virus serotypes Asia1 in Bangladesh and VP1 protein heterogeneity with vaccine strain IND 63/72. (1st February 2015) - Ullah, H.; Siddique, M.A.; Al Amin, Md.; Das, B.C.; Sultana, M.; Hossain, M.A.
Abstract: Foot‐and‐mouth disease virus (FMDV) serotypes O, A and Asia1 are responsible for significant number of disease outbreaks in Bangladesh; however serotype Asia1 has not been reported in circulation since 1996. The present investigation reports the detection of serotype FMDV Asia1 from local farms in 2012 and 2013 outbreaks. The farms were located in Jessore and Gazipur districts, and one of these farms was under vaccine control programme. Phylogenetic analysis of the complete VP1 gene revealed that FMDV Asia1 is under genetic lineage C having close similarity to the Asia1 sequences of Indian origin. The circulatory genotype Asia1 showed VP1 protein sequence heterogeneity of eight amino acid substitutions within the G‐H loop with the vaccine strain [IND 63/72 (AY304994)] used in vaccination programme. ELISA assay revealed that, of seven, only one local field serum sample (cattle vaccinated 38 days earlier) was positive at a titre level of >2·4 (log10) but failed to protect the cattle from infection occurred by the virus. This investigation focused that the eight amino acid substitution in VP1 protein at G‐H loop of the locally circulated FMDV serotype Asia1 strain may be a reason for current vaccination failure. Significance and Impact of the Study: This study presents the first report of the re‐emergence of foot‐and‐mouth disease virus (FMDV) serotype Asia1 in Bangladesh after 1996. Bangladesh loses as much as US$125 million annually due to FMD. Vaccination is one of the effective strategies to prevent FMDV infection, and in Bangladesh, this practice is carried out in limited scale by imported vaccines. Vaccination failure has occurred due to the imported vaccine consist of FMDV strain(s) of different genetic lineage than locally circulated FMDV type Asia1. So this study encourages the local vaccine development targeting local circulatory FMD virus.